TTF–PTM dyads: from switched molecular self assembly in solution to radical conductors in solid state. Issue 2 (28th September 2016) - Souto, Manuel; Rovira, Concepció; Ratera, Imma; Veciana, Jaume
Abstract : Dyads formed by tetrathiafulvalene (TTF) linked to perchlorotriphenylmethyl (PTM) radicals exhibit interesting physical properties such as bistability in solution or conductivity in solid state. Abstract : Organic donor–acceptor (D–A) systems formed by the electron-donor tetrathiafulvalene (TTF) linked to the electron-acceptor perchlorotriphenylmethyl (PTM) radical through different π-conjugated bridges exhibit interesting physical properties such as bistability in solution or conductivity in solid state. Understanding the interplay between intra- and intermolecular charge transfer processes in solution is of high interest in order to rationalize the self-assembling ability and conducting properties of such dyads in solid state. In this Highlight we examine the self-assembling properties of different TTF–π–PTM radical dyads that have potential applications as molecular switches or conductors in the field of molecular electronics.